CONTRIBUTION OF LEARNING INTEREST AND THE LEARNING ENVIRONMENT TO STUDENT LEARNING OUTCOMES IN ECONOMIC LESSONS AT SMA EKASAKTI PADANG - Agustina Agustina (JOURNAL INTERNATIONAL ON GLOBAL EDUCATION, 2022)
This research is motivated by the not yet optimal learning outcomes in the Economics subject of class XI Social Sciences SMA Ekasakti Padang, where some students get learning outcomes below the minimum completeness criteria, namely 78 with a range of 0 - 100. The purpose of this research is to reveal the contribution of interest in learning and the learning environment. on student learning outcomes in economic subjects at SMA Ekasakti Padang. This type of descriptive correlational research. The results showed: (1) Interest in learning contributed 21% to learning outcomes; (2) the learning environment contributes 47.6% to learning outcomes; and (3) the percentage contribution of interest variables (X1)and learning environment (X2)together to student learning outcomes (Y) is 50.3%. This shows that the better the interest and learning environment, the better student learning outcomes will be.